2012
DOI: 10.1100/2012/857249
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-Producing Bacteria from a Sand Dune Ecosystem and the Effect of Sodium Benzoate on Siderophore Production by a Potential Isolate

Abstract: Bioremediation in natural ecosystems is dependent upon the availability of micronutrients and cofactors, of which iron is one of the essential elements. Under aerobic and alkaline conditions, iron oxidizes to Fe+3creating iron deficiency. To acquire this essential growth-limiting nutrient, bacteria produce low-molecular-weight, high-affinity iron chelators termed siderophores. In this study, siderophore-producing bacteria from rhizosphere and nonrhizosphere areas of coastal sand du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…In addition, fine-tuning of siderophore secretion (up-or down-regulation) in response to available carbon sources (aromatic or non-aromatic) provides an additional fitness advantage to P.putida by curtailing unproductive energy expenditure for siderophore secretion where it is not warranted. Our hypothesis can be further supported by two observations: Jin et al (2010) have shown a significant increase in siderophore secretory microbes in iron-limited, phenolic-rich rhizospheric environments, while Gaonkar et al (2012) have shown a significant increase in siderophore secretion in response to sodium benzoate in marine isolates. These observations have indirectly provided a link between siderophore secretion and aromatic utilization.…”
Section: Resultssupporting
confidence: 70%
“…In addition, fine-tuning of siderophore secretion (up-or down-regulation) in response to available carbon sources (aromatic or non-aromatic) provides an additional fitness advantage to P.putida by curtailing unproductive energy expenditure for siderophore secretion where it is not warranted. Our hypothesis can be further supported by two observations: Jin et al (2010) have shown a significant increase in siderophore secretory microbes in iron-limited, phenolic-rich rhizospheric environments, while Gaonkar et al (2012) have shown a significant increase in siderophore secretion in response to sodium benzoate in marine isolates. These observations have indirectly provided a link between siderophore secretion and aromatic utilization.…”
Section: Resultssupporting
confidence: 70%
“…The siderophore-producing strain of JFW16 was identified via the chrome azurol sulphonate (CAS) assay (Gaonkar et al 2012). …”
Section: Analysis Of Cas Assays and Rhizospheric Ph Valuesmentioning
confidence: 99%
“…Interestingly both pyoverdine and azotobactin are mixed ligand siderophores. Studies have shown that fluorescent pigment pyoverdine from Pseudomonas aeruginosa is one such example that is known to be a powerful scavenger and efficient transporter of Fe(III) [23][24][25]. In the current investigation, the ability of the pigment to chelate iron from the CAS medium was studied.…”
Section: Ability Of the Pigment To Chelate Ironmentioning
confidence: 94%